Childhood Adversity, Self-Esteem, and Diurnal Cortisol Profiles Across the Life Span. (September 2016) - Zilioli, Samuele; Slatcher, Richard B.; Chi, Peilian; Li, Xiaoming; Zhao, Junfeng; Zhao, Guoxiang
Childhood adversity is associated with poor health outcomes in adulthood; the hypothalamic-pituitary-adrenal (HPA) axis has been proposed as a crucial biological intermediary of these long-term effects. Here, we tested whether childhood adversity was associated with diurnal cortisol parameters and whether this link was partially explained by self-esteem. In both adults and youths, childhood adversity was associated with lower levels of cortisol at awakening, and this association was partially driven by low self-esteem. Further, we found a significant indirect pathway through which greater adversity during childhood was linked to a flatter cortisol slope via self-esteem. Finally, youths who had a caregiver with high self-esteem experienced a steeper decline in cortisol throughout the day compared with youths whose caregiver reported low self-esteem. We conclude that self-esteem is a plausible psychological mechanism through which childhood adversity may get embedded in the activity of the HPA axis across the life span.